Making sense of motherhood : a narrative approach - Miller, Tina, 1957- (Cambridge University Press, 2005)
This book explores how women try to make sense of, and narrate their experiences of first-time motherhood in the Western world. It charts the social, cultural and moral contours of contemporary motherhood and engages with sociological and feminist debates on how selves are constituted, maintained and narrated.